Colonising her cultural identity : geographies of a hybrid identity in colonial Turanga : a thesis presented to Massey University, Palmerston North, New Zealand in fulfilment of the requirements for the degree of Master of Arts in Geography - Wyse, Stephanie (Massey University, 2002)
This thesis is a feminist historical geography of the construction of a woman's identity in Turanga (now known as Gisborne), New Zealand from 1840 to 1893. Using textual analysis of private and public documents from the time period, it reveals socio-spatial power structures, cultural relations, and gender relations of the place and time, and the ways in which they contribute to the conditions necessary for a fluid cultural identity. The research finds that three key conditions of cultural hybridity proposed by Homi K. Bhabha are applicable to a subject of the place and time period, Keita Wyllie. The thesis further argues that a fourth condition is necessary, namely the role of space as an active and constituent agent in the process of identity formation. The research complements previous histories of the East Coast/Turanga region by examining issues of cross-cultural identity, power structures and gender relations previously absent from historical accounts of the area.
Keywords: Wyllie, Keita; Māori; Gisborne District - history; Women; Māori Master's Thesis